Crabs of the families Palicidae and Crossotonotidae (Crustacea, Decapoda, Brachyura, Palicoidea) from the Ogasawara Islands, Japan, with the description of a new species - Takeda, Masatsune; Tachikawa, Hiroyuki (Zootaxa, 2015)
Four species of palicoid crabs, Neopalicus jukesii (White, 1847) and Rectopalicus ampullatus Castro, 2000 of the family Palicidae, and Crossotonotus spinipes (De Man, 1888) and a new species of Pleurophricus A. Milne-Edwards, 1873 of the family Crossotonotidae, are recorded from the Ogasawara Islands, Japan. Diagnostics for the new species are the protruded bilobed front, six subacute lobate teeth at each lateral margin of the carapace, six rounded lobes at the posterior margin of the carapace, a crested armature of the cheliped carpus, and the strongly depressed ambulatory legs, which readily distinguish it from its two congeners, P. cristatipes A. Milne-Edwards, 1873 known by two males from Australia and the Kai Islands in Indonesia, and P. longirostris (Moosa & Serène, 1981) known by a female from the Sunda Strait, Indonesia.